A validation study of driving errors using a driving simulator. (February 2015) - Meuleners, Lynn; Fraser, Michelle
Highlights: On-road and simulator (UC/Win-road software) driving performance were compared. There was no difference between on-road and simulator performance for many outcomes. Results provide early support for the relative validity of the driving simulator. Abstract: Background: Driving simulators have become an important research tool in road safety. They provide a safer environment to test driving performance and have the capacity to manipulate and control situations that are not possible on-road. Aim: To validate a laboratory-based driving simulator in measuring on-road driving performance by type and mean driving errors. Methods: Participants were instructed to drive a selected route on-road. The same route was programmed in the driving simulator using the UC/Win-road software. All participants completed a background questionnaire. On-road driving behaviours of participants and driving behaviours in the simulator were assessed by an occupational therapist and two trained researchers using an assessment form. Interclass correlations were calculated to assess the inter-rater agreement between the researchers on driving behaviours. Paired t -tests were used to assess differences in driving performance between the simulator and on-road assessments. Results: A convenience sample of 47 drivers aged 18–69 years who held a current Western Australian class C licence (passenger vehicle) were recruited into the study. The mean age was 34.80 years (SD: 13.21) with twenty-six males (55.32%) and 21 females (44.68%) completing the study. There was no statistical difference between the on-road assessment and the driving simulator for mirror checking, left, right and forward observations, speed at intersections, maintaining speed, obeying traffic lights and stop signs. Conclusion: The preliminary results provide early support for the relative validity of the driving simulator which may be used for a variety of road safety outcomes with reduced risk of harm to participants.